Análise de migração de consumidores residenciais para a tarifa branca em sistemas de distribuição de energia elétrica - Silva, Natalí Nunes dos Reis da (2018)
This study analyzes the impact caused by the load curve at peak times, due to the adhesion by residential consumers to the white fare. The white fare is a measure belonging to the Demand Side Management (DSM) actions; it is a fare-based proposal of demand response. To determine these impacts, several simulations were performed considering different consumer compliance scenarios belonging to a real distribution system. The results obtained in the simulations indicate that, for a residential adhesion of up to 10%, there are no significant differences in the load curve at peak times; for adhesion between 10% and 50%, the differences are small, but they do not require large changes in the network to be absorbed; and only in extreme scenarios with more than 75% of users' adherence, it would be necessary to consider this measure in the medium and long term expansion planning of the distribution systems.